2000
DOI: 10.1007/s000660050051
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiation with Concurrent 5-Fluorouracil for Locally Advanced T4-Primary Rectal Cancer

Abstract: A combination of high-dose preoperative radiochemotherapy followed by extended surgery can achieve clear resection margins in more than 80% of patients with locally advanced cT4 rectal tumor. An encouraging trend evolves for this multimodality treatment to improve long-term local control and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
2
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 20 publications
(20 reference statements)
2
34
2
7
Order By: Relevance
“…In patients with locally advanced, primarily irresectable cancer (i.e. a cancer where a complete gross surgical clearance is deemed unlikely to be achieved), preoperative CRT has been used to cause tumour regression to such an extent that the cancer can be removed radically with adequate clearance in the resection margin (Videtic et al, 1998;Chan et al, 2000;Rodel et al, 2000).…”
mentioning
confidence: 99%
“…In patients with locally advanced, primarily irresectable cancer (i.e. a cancer where a complete gross surgical clearance is deemed unlikely to be achieved), preoperative CRT has been used to cause tumour regression to such an extent that the cancer can be removed radically with adequate clearance in the resection margin (Videtic et al, 1998;Chan et al, 2000;Rodel et al, 2000).…”
mentioning
confidence: 99%
“…In addition, it was suggested that extracolonic invasion is not necessarily a poor prognostic factor (11). Rödel et al (12) reported that curative operations may be performed on 94% of patients with contiguous or adherent-to-adjacent pelvic organs, following CRT with 5-fluorouracil regimen. A resection of the pelvic tumor with negative margins was achieved in 84% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the locally advanced tumors (T3, T4 or N+) the surgery is combined with preoperative radiotherapy (RT), which leads to better local control of the disease and to improved survival compared with surgery alone (1,2). Randomized trials have demonstrated, that the outcomes of concomitant chemoradiotherapy (CHT/RT) are superior to the radiotherapy alone (3). The EORTC phase III trial compared radiotherapy alone with radiotherapy combined with chemotherapy (CHT) consisting of administration of 5-fluorouracil and leucovorine (FUFA) as a bolus in weeks 1 and 5.…”
Section: Introductionmentioning
confidence: 99%